Humanity and Resilience Project: The Development of a New Outreach Program for Counseling Centers at Colleges and Universities. Issue 1 (2nd January 2019) - Sibley, Stephanie; Sauers, Lindsay; Daltry, Rachel
ABSTRACT: When determining how best to help reduce the distress that exists among today's college students, it is believed that proactive, on-campus programming is a beneficial supplement to on-campus resources that are often utilized after concerns already exist. Helping students develop resiliency skills is one proactive measure that is believed to improve students' well-being and ability to cope with adversity. Thus, the Humanity and Resilience Project at West Chester University was recently developed with the goal of helping to promote resiliency among students by encouraging genuine social connections that include a sense of shared vulnerability and humanity. With literature that supports the rationale for this approach, it is hoped that the following description of the development and implementation of this project will inspire other college campuses to consider similar programming for their students.